Halle Motley: capstone - Motley, Halle, artist (Colorado State University. Libraries, 2025)
The artist's statement: My work is inspired by the transformative power of narrative. I take stories rich with meaning and emotion, and translate them into a physical form. Through metal, stones, and time, I strive to transport the viewer into the narrative while also triggering their mind to process and think about the narrative in new ways. My practice is deeply influenced by religious art's historical role in non-literate societies, where visual elements bridged gaps between written scripture and public understanding. Such art transcended language, class, and age barriers, whether sharing stories broadly or preserving them for select audiences. In this tradition, I distill complex narratives, religious, historical, emotional, personal, into digestible visual elements that can be both viewed and worn. My work tells the story of pivotal moments in my personal life and in the grander scheme of time, all that radically shape who I am. My recent body of work draws inspiration from my transformative trips, how they deepened my relationship with God, and changed my view of life. Witnessing how ancient stories manifested both through centuries-old artwork and in the natural landscape revealed complementary interpretations that I now weave together to share these narratives with contemporary audiences. Each technique, fabrication, gem or stone setting, or casting, is chosen specifically to enhance the storytelling. For example bronze has rich associations to historical transformation and artistic tradition, and carries cultural weight that influences perception. When I use bronze, I hope that the long history of bronze being used in sculptures as well as in the foundations of society are brought to one's mind. Every metal and stone embodies meaning that I deliberately harness. Through these material choices and techniques, I create objects that communicate stories, while honoring the ancient tradition of making meaning tangible.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing; jewelry design